Challenging the Frontiers of African Integration the Dyanmics of Policies, Politics and Transformation in the East African Community - Mwapachu, Juma V. (Dar es Salaam E&D Publishing, 2012)
The basic premise of this book is that regional integration in Africa offers great promise in addressing endemic poverty in advancing Africa's integration in the global economy. Based on hands on experience of the author and a body of research focusing on the East African Community, the book breaks the path in providing a wealth of information and analysis of cutting edge topical issues on Africa's emergent promise, as well as on the challenges that confront Africa and EAC in particular in achievingdeeper economic and political integration. The EAC model of integration, with its unique and lofty but overly ambitious goal of political federation, evidently offers exciting possibility for the broader quest for the African Economic Community and the United States of Africa. However, there are alsoclear lessons, marked by challenges of Zero sum game mindsets and sovereignty sensitivities that slow down and even hamper what would make the Eac process more robust and rewarding and with important bearing on Africa's own continental ambitions. From a broad analytical perspective that embraces diverse roles of state institutions,local governments,business,media,civil society and education. The book ably charts out the critical factors that underpin and drive succesful regional integration. It offers deep and rare analysis and insights of the role of management and leadership in leading a complex and politically driven inter-governmental organisation. A notable feature of the book is the coverage of the historical development of the COMESA-EAC-SADC Tripartite Framework, a novel idea in the attempt to address the dysfunctions of multiple memberships of Regional Economic Communities in Africa and the Pragmatic and progressive approach towards building a fast paced movement for the realisation of the African Economic Community
Includes Index(402-414)
Keywords: Integration, East African Community Transformation Africa